Feeding behaviour of Trumpeter Swans Cygnus buccinator - Grant, Todd A; Henson, Paul; Cooper, James A (Wildfowl, 1997)
We used activity time-budgets to study the feeding behaviour of Trumpeter Swans breeding during 1988-1989 on the Copper River Delta, Alaska. Local foods were proximally important for pre-nesting and incubation activities. Females spent more time feeding and had longer feeding bouts than males during pre-nesting, but the pattern was reversed during incubation. During short incubation recesses, females fed with more intensity than males. Although physiologically capable of extended periods of fasting, females appear to rely, in part, on exogenous foods to supplement energy demands of egg laying and incubation. Pairs with young fed less and had shorter feeding bouts than failed breeders, foregoing some feeding opportunities to care for their young. Males fed less and were more vigilant than females during brood rearing, allowing females and young more time to feed undisturbed. Feeding was the principal prefledging activity of cygnets. Cygnet feeding and non-feeding periods alternated regularly and were relatively uniform in length over time and among broods. The rate at which cygnets can physiologically process green vegetation probably limits the rate of food intake.